Does Play-Based Learning Support Children’s Everyday Resiliency? A Cross-Case Analysis of Parents’ and Kindergarten Teachers’ Perceptions of Play-Based Learning as a Precedent to Young Children’s Coping During the Pandemic-Affected 2020–2021 School Year - Lisa Fyffe; Angela Lewis (Children)
Background: Play has long been credited with fostering self-regulation in young children, though few studies have examined how children draw upon early childhood experiences with play to navigate adversity later in childhood. The purpose of this study is to describe the facets of the children’s everyday resiliency that were attributed to their play-based experiences by parents and teachers as they reflected on the children’s kindergarten experiences during the COVID-19 pandemic. Methods: We used a cross-case study design to examine the positive coping strategies parents and teachers observed in three five-year-old girls and one six-year-old boy entering kindergarten during the 2020–2021 pandemic-affected school year. We recruited parent participants based on their child’s enrollment at a Reggio Emilia-inspired, play-based early childhood center in Northern Colorado for three or more years prior to entering kindergarten. Once parents enrolled in the study, we extended an invitation to their child’s kindergarten teacher to participate. Data included three one-hour interviews with each participant, field visits during remote learning, and artifact collection over the course of the school year. Results: Cross-case analysis revealed four themes: “Willing to Adjust”, “Understands the Situation”, “Uses Advanced Language”, and “Embraces Challenge”. Participants describe these children as willing to adjust to public health orders, having a deep understanding of the pandemic’s societal repercussions, using sophisticated language to process adversity, and embracing the challenge of becoming kindergarteners. Conclusions: Participants believed these children’s experiences with play-based learning promoted the interdisciplinary development of their social language, persistence, altruism, and cognitive flexibility; these traits fostered the children’s positive coping strategies throughout the pandemic-affected kindergarten year.